1999
DOI: 10.1007/s002040050634
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of apoptosis and induction of DNA synthesis in vitro by the phthalate plasticizers monoethylhexylphthalate (MEHP) and diisononylphthalate (DINP): a comparison of rat and human hepatocytes in vitro

Abstract: Diethylhexylphthalate (DEHP) and diisononylphthalate (DINP) are plasticizers with many important commercial, industrial and medical applications. However, both DEHP and DINP are rodent peroxisome proliferators (PPs), a class of compounds that cause rodent liver tumours associated with peroxisome proliferation, induction of hepatic DNA synthesis and the suppression of apoptosis. Despite these effects in the rodent, humans appear to be nonresponsive to the adverse effects of PPs. Previously, we have shown that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 22 publications
1
25
0
2
Order By: Relevance
“…While the induction of peroxisomal genes in vitro in rodent hepatocytes is robust and comparable to that in whole liver [43,44], the increase in DNA synthesis, a marker of cell proliferation in vitro has been reported to be only 120-200%, which is markedly less than that observed in vivo [43,44]. Suppression of apoptosis studies in cultured rat hepatocytes were conducted under both "spontaneous" and growth factor (e.g., TGFβ1)-induced conditions [43,44,31].…”
Section: Pleiotropic Responses To Dehp In Vitro In Cultured Hepatocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…While the induction of peroxisomal genes in vitro in rodent hepatocytes is robust and comparable to that in whole liver [43,44], the increase in DNA synthesis, a marker of cell proliferation in vitro has been reported to be only 120-200%, which is markedly less than that observed in vivo [43,44]. Suppression of apoptosis studies in cultured rat hepatocytes were conducted under both "spontaneous" and growth factor (e.g., TGFβ1)-induced conditions [43,44,31].…”
Section: Pleiotropic Responses To Dehp In Vitro In Cultured Hepatocytesmentioning
confidence: 99%
“…It was concluded that hepatocytes from all species included in the study were responsive to MEHP by inducing peroxisomal palmitoyl-CoA oxidase, but rat hepatocytes were about 30-fold more sensitive based on the dose-response studies. The effects of MEHP on human hepatocytes have also been studied in vitro by several groups [43,44,31]. A general conclusion from these experiments is that human hepatocytes are largely non-responsive to MEHP when DNA synthesis, apoptosis, or peroxisomal gene induction are evaluated.…”
Section: Pleiotropic Responses To Dehp In Vitro In Cultured Hepatocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ayrıca, MEHP'nin transforme edici büyüme faktörü [transforming growth factor (TGFβ1)] ve DNA'da hasar oluşturucu ajanlar olan etoposid, hidroksiüre ve anti-Fas antikorlarıyla indüklenen karaciğer apoptozunu da baskıladığı gösterilmiştir. 34,[39][40][41] Sıçan hepatositleri üzerinde yapılan canlılık deneylerinde, peroksizom proliferatörlerine maruz kalan hepatositlerin en az dört hafta canlı kaldığı; ancak kontrol hayvanlardan elde edilen hücrelerin ortalama sekiz gün canlı kalabildiği; peroksizom proliferatörlerine maruz kalan kültürlerde apoptoz belirtilerinin (kondense ve fragmante DNA) daha az sıklıkla görüldüğü belirtilmiştir. 42 PPAR-α'nın apoptozun inhbisyonu için gerekli olduğu düşünülmektedir ve PPAR-α-farelerin nafenopin gibi peroksizom proliferatörleri-nin etkilerine yanıt vermediği, spontan ve TGFβ1 ile indüklenen apoptoza açık olduğu belirtilmiştir.…”
unclassified
“…42 PPAR-α'nın apoptozun inhbisyonu için gerekli olduğu düşünülmektedir ve PPAR-α-farelerin nafenopin gibi peroksizom proliferatörleri-nin etkilerine yanıt vermediği, spontan ve TGFβ1 ile indüklenen apoptoza açık olduğu belirtilmiştir. 34,40 PPAR-α aracılıklı apoptoz inhibisyonu bu reseptö-rün negatif efektör regülatör etkisine bağlıdır. 42 …”
unclassified